THE APPEARANCE OF POSTMODERN CHARACTERISTICS IN THE NOVEL "DANIEL MARTIN" BY JOHN FOWLES - Sodikova Bakhtigul Ibodyullayevna (Western European Studies, 2024)
The theme of this novel's complicity in the creation and promotion of masculine stereotypes of women was already foreshadowed in FLW, but it is most evident in this book. This is because this book focuses on writing fiction. As shown, while fiction can help deconstruct some meta-narratives, the author himself (here deliberately masculine pronoun) sometimes promotes the very stereotypes he seeks to deconstruct. . In Daniel Martin, Fowles literally portrays his character Daniel Martin (Dan) as he struggles to form his own identity and art, to find a sense of unity, to see life and himself fully. z and describes his metaphorical quest and self-discovery. In this sense, the fragmented and continuous narrator in the novel, the abundance of characters, scenes and events, the shifting of time and space, the simultaneous movement forward and backward reflect the unique features of the postmodern novel
Keywords: fragmentation; characters; scenes and events; settings and events